Estudo do comportamento da PIO de 24 horas e frequência de glaucoma em pacientes com síndrome da apnéia obstrutiva do sono - Bet de Moraes Silva, Maria Rosa [UNESP] (2009)
Purpose: To determine the frequency of glaucoma and evaluate the behavior of 24-hour intraocular pressure in patients with the obstructive sleep apnea syndrome (OSAS). Methods: Eleven consecutive patients with OSAS, diagnosed by polysonography, were avaliated in a cross-sectional study. Demographic data were analyzed: age, sex, race/color, weight, height and associated diseases. The patients were submitted to complete ophthalmologic examination, including the visual field, as well as to 24-hour intra-ocular pressure (IOP) evaluation by an applanation tonometer at 9h, 12h, 15h, 18h, 24h and 6h in the lying and sitting positions. The diagnostic criterion for glaucoma was alteration of the visual field (VF) compatible with glaucoma and one or more of the following alterations: cup-disc ratio >= 0.7, hemorrhage, wedge-shaped defect, bayonet-shaped vessels, Hoyt's sign, asymmetry > than 0.2 between cup/disc ratio of the eyes. The angle should be opened without alterations. Results: 9 (82%) of 11 patients showed glaucoma or were suspected to have glaucoma, 9% of which exhibited normal tension glaucoma and 73% were suspected to have glaucoma for presenting alterations in the optic nerve or ocular hypertension. The mean for the IOP values of the 11 patients was observed to be the highest at 6 o'clock, when they were lying down. Variations of IOP >= 5 mmHg occurred in 7 (64%) of the patients, and variations of up to 14 mmHg and IOP peaks of up to 32 mmHg were observed. Conclusion: OSAS may be an important risk factor for the development of glaucoma, particularly that of normal tension glaucoma. Patients with OSAS must be referred to an ophthalmologist and those professionals must be attentive to the association of sleep disorders in patients with open-angle glaucoma.